The Efficacy of Moxifloxacin-containing Triple Therapy after Hybrid Therapy Failure in Helicobacter pylori Eradication - Soohoon Kwon (The Korean Journal of Gastroenterology, 2017)
Background/Aims: Hybrid therapy was successful in eradicating Helicobacter pylori (H. pylori) according to previous reports. However, to the best of our knowledge, there have only been a few studies evaluating the optimal choice after hybrid failure. Hence, we aimed to evaluate the efficacy of moxifloxacin-containing triple therapy after hybrid therapy failure in H. pylori eradication. Methods: Between January 2013 and March 2016, we retrospectively reviewed patients who underwent failed hybrid therapy, as first line treatment, in eradicating H. pylori (rabeprazole and amoxicillin b.i.d for 14 days, in addition to clarithromycin and metronidazole b.i.d for final 7 days). Then, we investigated the eradication rates of moxifloxacin-containing triple therapy (rabeprazole, amoxicillin b.i.d and moxifloxacin qd) as the second line of treatment. Intention-to-treat (ITT) and per-protocol (PP) analyses were used to determine the eradication rate. We evaluated the status of H. pylori by using 13C-urea breath test 6 weeks after the final treatment. Moreover, compliance and adverse effects of each patient were analyzed. Results: Among those who failed the initial hybrid therapy, 11 patients received moxifloxacin-containing triple therapy. The overall eradication rates, as determined by ITT and PP, were 72.7% (n=8/11) and 80% (n=8/10), respectively. The compliance rate was 100%, and there were no serious adverse effects. Conclusions: Moxifloxacin-containing triple therapy can be used as a second line therapy in case of hybrid therapy failure. A large scale study is necessary to confirm the findings of this study and establish clinical evidence.